Factors Influencing the Adoption of Automating Systems in the Facilities Management of High-Rise Buildings in Lagos, Nigeria - Awosode, Orayinka; Ajayi, Cyril (Journal of African Real Estate Research, 2023)
Purpose: The paper examined factors influencing the choice of automating systems in high-rise buildings in Lagos, Nigeria with a view to providing information that could enhance facility management practice. Design/Method/Approach: The study is a quantitative research, administering 53 copies of questionnaire on resident facility managers of selected high-rise buildings in Lagos with a response rate of 77.4%. Simple frequency distribution, percentage (%) weighted mean score on 5 point-Likert scale measurement and factor analysis were used to analyze responses. Findings: The study revealed that the choice of automating systems used by facility managers was significantly influenced by the cost of acquisition of the automating system, while the need to protect buildings against failure was considered as the most significant factor influencing the adoption of automation in the management of facilities in high-rise buildings. Practical Implication: The use of automating systems presents facility managers innovative ways of ensuring functionality of the built environment through the integration of people, place, process and technology. Originality: The study contributes to the frontier of knowledge on the adoption of automation in the facility management of high-rise buildings.